Selective Catalytic Oxidation of Diphenol by Metal-Organic Frameworks Cu3(BTC)2 Using Hydrogen Peroxide - Wu, Yun; Yang, Benhong; Li, Meng; Wang, Wei; An Tian, Chang (Asian Journal of Chemistry, 2014)
Catalytic oxidation of hydroquinone and pyrocatechol using hydrogen peroxide by metal-organic frameworks of Cu3(BTC)2(H2O)3 with an average size of 1 nm. Significant selectivity was showed in the catalytic oxidation of hydroquinone and pyrocatechol. Also we mainly discussed the influences of reaction temperature and medium to the selectivity by kinetics methods. It was concluded that reaction medium had lager influence on selectivity than temperature.